Efficient photothermal catalytic hydrogen production via plasma-induced photothermal effect of Cu/TiO2 nanoparticles. (22nd February 2023) - Li, Jinghua; Hatami, Mohammad; Huang, Yalong; Luo, Bing; Jing, Dengwei; Ma, Lijing
Abstract: Developing appropriate photocatalyst with high efficiency is still the basic strategy for practical application of emerging technology. Herein, non-noble metal copper (Cu) nanoparticles were in situ hybrided with TiO2 by a chemical reduction method. The crystal phase and structure were characterized by XRD, SEM, and TEM measurements. Hydrogen production results showed that Cu nanoparticles significantly improved the photocatalytic hydrogen production rate. The hydrogen production rate was as high as 24160.69 μmol g −1 h −1 at 100 °C, which was 36.25 and 8.46 times higher than the hydrogen production rates of pure TiO2 and 0.13 wt% Cu/TiO2 at room temperature, respectively. PL spectra, UV–vis spectra, IR images and photoelectrochemical measurements showed that the plasma-induced photothermal effect of Cu/TiO2 nanoparticles, which raised the temperature of the reaction system and promoted photothermal catalytic performance. Briefly, this work provides a facile fabrication method of noble-metal-free photocatalysts featuring in low-cost and high efficiency. In the future, coupling the photothermal effect of plasmonic Cu to further speed up the kinetics should be another promising research direction for further improving hydrogen production. Highlights: Non-noble metal copper (Cu) nanoparticles were in situ hybrided with TiO2 . The crystal phase and structure were characterized by XRD, SEM, and TEM. Results showed Cu nanoparticles improved the photocatalytic hydrogen production. Plasma-induced photothermal effect of Cu/TiO2 nanoparticles raised temperature. A facile fabrication method of noble-metal-free photocatalysts is performed.